1996
DOI: 10.1016/s0092-8674(00)81391-4
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric Rings of the Sec61p Complex Induced by Ligands Required for Protein Translocation

Abstract: The heterotrimeric Sec61p complex is a major component of the protein-conducting channel of the endoplasmic reticulum (ER) membrane, associating with either ribosomes or the Sec62/63 complex to perform co- and posttranslational transport, respectively. We show by electron microscopy that purified mammalian and yeast Sec61p complexes in detergent form cylindrical oligomers with a diameter of approximately 85 A and a central pore of approximately 20 A. Each oligomer contains 3-4 heterotrimers. Similar ring struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
253
1
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 323 publications
(271 citation statements)
references
References 36 publications
15
253
1
2
Order By: Relevance
“…A possible interpretation is that this Sec61 population is in a lower oligomeric state, likely corresponding to monomers or dimers. Freeze-fracture experiments with proteoliposomes support the idea that the formation of Sec61-oligomers may be induced by ribosome binding (Hanein et al, 1996). Different quaternary states of the bacterial homologue SecYEG in the membrane have also been described, and their relative abundance may change during translocation (Bessonneau et al, 2002;Scheuring et al, 2005).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…A possible interpretation is that this Sec61 population is in a lower oligomeric state, likely corresponding to monomers or dimers. Freeze-fracture experiments with proteoliposomes support the idea that the formation of Sec61-oligomers may be induced by ribosome binding (Hanein et al, 1996). Different quaternary states of the bacterial homologue SecYEG in the membrane have also been described, and their relative abundance may change during translocation (Bessonneau et al, 2002;Scheuring et al, 2005).…”
Section: Discussionmentioning
confidence: 78%
“…Although these connections can each break and reform, as suggested by the ATA experiments, collectively they keep the ribosome firmly bound to the membrane, explaining the extremely slow dissociation rate in the absence of ATA. Interestingly, the Sec61-oligomers in RMs are not disassembled upon removal of the ribosomes by treatment with puromycin/high salt (Hanein et al, 1996), which may explain why PK-RMs retain highaffinity sites for ribosomes. The ribosome-bound, tetrameric Sec61 population seems to be interconvertible with a free Sec61 population that binds ribosomes and RNCs lacking SRP only poorly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Sec61 channel is formed by four or five Sec61 complexes that assemble in the ER membrane for protein import into the ER in response to the presence of a functional signal peptide or in the presence of the Sec63 complex, which is required for posttranslational protein import into the yeast ER (Hanein et al, 1996). The Sec61 channel is sealed at both ends to maintain the permeability barrier across the ER membrane (Hamman et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In both of these protein export machines, microscopic, biochemical and biophysical studies have shown the translocon complexes to be arranged around a central cavity estimated to range between 9 and 60 Å , depending on the translocation status of the channel. (8)(9)(10)(11) To maintain the permeability barrier provided by the membrane, passage through pores of such large diameter must be controlled. The mode of regulation is dependent on whether translocation is coupled to protein translation or rather occurs following the translation event.…”
Section: Introductionmentioning
confidence: 99%